Advertising Budget Allocation under Uncertainty - Holthausen, Duncan M.; Assmus, Gert (Management Science, 1982)
This article presents a model for the allocation of an advertising budget to geographic market segments, or territories, when the sales response to advertising in each segment is characterized by a probability distribution. It is shown that allocation decisions that are based on the expected sales response may be associated with a relatively large degree of risk and, therefore, non-optimal to a risk-averse manager. The model derives an “efficient frontier” in terms of the expected profit and its variance resulting from alternative budget allocations. The manager then chooses the optimal allocation based on his/her preference function.